Analysis of Kidney Tissue Keting Mystus gulio (Hamilton, 1822) in Gembong and Rejoso River, Pasuruan, Indonesia - Chandika Lestariaji; Endang Yuli Herawati; Diana Arfiati; Saddam Langkung Djaduk; Priska Ristianadewi; Aang Setyawan Anjasmara; Rahmi Valina (Postgraduate, University of Mataram, 2024)
Mystus gulio is a local fish that can open up opportunities for the community. Pollution causes water quality to decrease. Fish are an important indicator in the aquatic environment, Histological analysis can be said to have a function as a natural biological sign to determine the health condition of fish which can be seen from changes in tissue structure in organs exposed to pollutants. Organs that’s vulnerable to water pollution is kidneys. Kidney tissue is susceptible to damage because kidneys function as a means of filtration and excretion, The method used in this research is descriptive method. Fish were caught from river than dissected to remove the kidneys for histopathological analysis using the HE method, analyzed using the scoring method. The results obtained in both rivers were that fish kidneys caught in the Gembong River were categorized as moderately damaged, while fish kidneys caught from the Rejoso River were categorized as lightly damaged. This is in line with the results of the heavy metal lead from both rivers. Where the yield of lead in fish kidneys caught from the Gembong is on average higher than the yield from fish kidneys caught from the Rejoso.